Rediagnosis of Callianideidae and its genera (Crustacea: Decapoda: Axiidea), and description of a new species of Heardaxius Sakai, 2011 - Poore, Gary C. B. (Zootaxa, 2015)
Callianideidae and Thomassiniidae, two families of Axiidea, are synonymised and Callianideidae diagnosed. The six genera, Callianidea H. Milne Edwards, 1837, Crosniera Kensley & Heard, 1991, Mictaxius Kensley & Heard, 1991, Heardaxius Sakai, 2011, Paracallianidea Sakai, 1992 and Thomassinia de Saint Laurent, 1979 are diagnosed and all species listed. Garyia Sakai, 2011 is synonymised with Thomassinia. A key to genera is provided. A new species Heardaxius rogerbamberi is described from Papua New Guinea. Thomassinia aimsae Poore, 1997 is newly recorded from Papua New Guinea.